Introduction of the LEISA (Low External Input Sustainable Agriculture) System in Opaasi Village Comunities - Asminaya, Nur Santy; Bain, Ali; Aba, La; Arafah, Nur; Saili, Takdir; Badaruddin, Rusli; Putra, Agus Kurniawan (Universitas Negeri Semarang, 2023)
This community service activity aims to increase the knowledge and skills of the people of Opaasi Village, West Ranomeeto District, South Konawe Regency, Southeast Sulawesi Province in implementing the LEISA system. Methods for implementing this community service activity include: 1) Socialization of the LEISA system concept; 2. Demonstration on making alternative feed for ruminants; 3. Demonstration of making organic fertilizer; 4. Monitoring and Evaluation. During the activity, the community was very enthusiastic in listening to the presentation of the socialization material and was active in discussions, especially during technical guidance on making animal feed and organic fertilizer. At the end of the activity, the community in Opaasi Village has begun to slowly implement the LEISA system concept on integrated cattle farming land by using organic fertilizer on vegetable and ornamental plants and feeding cattle with ammoniated straw on a small and limited scale. This community service activity can increase the knowledge and skills of the Opaasi Village community in implementing LEISA. The positive impact currently felt by local communities is that they can provide healthy vegetables for consumption and provide animal feed in the dry season